Mobile health and implantable cardiac devices: Patients' expectations. (29th August 2020) - Villani, Giovanni Q; Villani, Andrea; Zanni, Alessia; Sticozzi, Concetta; Maceda, Diego Penela; Rossi, Luca; Pisati, Maria Sole; Piepoli, Massimo F
Abstract: Background: Mobile computing and communication technologies in health services and information (so-called mHealth) have modified the traditional approach in the follow-up of patients with implantable cardiac devices, increased patient engagement and empowerment, reduced healthcare costs and improved patients' outcome. Recent developments in mobile technology, with the introduction of smartphone-compatible devices that can measure various health parameters and transfer automatically generated data, have increased the potential application of remote monitoring and the interest towards mHealth. However, little is known about the patients' interest and expectations of this new technology. Objective: The patients' interest in the possibility of receiving data from their implantable cardiac device, clinical and health advice via remote monitoring on their smartphones were investigated. Methods: A questionnaire entitled 'Expectations for future possibility of self-management of device data' (Likert scale scored) was submitted to 300 consecutive implantable cardiac device outpatients. The questionnaire was focused on collecting patients' expectations in receiving direct information regarding their implantable cardiac device status (item 1, five questions), their own clinical status (item 2, seven questions) and advice on healthy lifestyle promotion (item 3, nine questions). Patient characteristics associated with greater interest towards mHealth were also investigated. Results: Questionnaires were completed by 268 patients (221 men, aged 69 ± 14 years). The Cronbach test reported an alpha value of 0.98 for item 1, 0.94 for item 2 and 0.97 for item 3. Patients declared to be mainly interested in the device interventions (62%) and in severe arrhythmia occurrence (61%), followed by data on heart failure severity (54%) and their performed physical activity (48%). Patients showed very little interest in ECG tracing (37%), but the lowest interest was expressed towards healthy lifestyle promotion advice (<40%). A higher education degree and the presence of the caregiver positively affected the interest towards remote monitoring information ( P < 0.001). Conclusions: The patients' interests were mainly directed at receiving information related to technical data of the implantable cardiac device and not to the overall management of the disease, underlying the insufficient awareness of patients towards the key role of self-control health status and the promotion of a healthy lifestyle.